The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/etc.2506
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of endosulfan on embryo‐larval development of the South American toad Rhinella arenarum

Abstract: Endosulfan is a widely used pesticide despite its extreme toxicity to a variety of taxa and its worldwide ban. The aim of the present study was to evaluate the acute and chronic toxicity of endosulfan on the embryonic-larval development of the common South American toad Rhinella arenarum. The results showed that lethal and sublethal effects increased with concentration and exposure time. The sensitivity to endosulfan increased during the larval period, the complete operculum stage (S.25) being the most sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
11
0
4
Order By: Relevance
“…In a recent publication (Svartz et al 2014), we reported the high toxicity of endosulfan to R. arenarum embryos and larvae with 504-h LC50 values of 0.03 (range 0.014-0.05) and 0.01 (range 0.006-0.015) mg L -1 , respectively. Moreover, we had characterized both lethal and sublethal effects of endosulfan on the embryo-larval development of R. arenarum, whereas in the present study we attempt to elucidate any correlation between developmental stage sensitivity and uptake of the pesticide.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In a recent publication (Svartz et al 2014), we reported the high toxicity of endosulfan to R. arenarum embryos and larvae with 504-h LC50 values of 0.03 (range 0.014-0.05) and 0.01 (range 0.006-0.015) mg L -1 , respectively. Moreover, we had characterized both lethal and sublethal effects of endosulfan on the embryo-larval development of R. arenarum, whereas in the present study we attempt to elucidate any correlation between developmental stage sensitivity and uptake of the pesticide.…”
Section: Discussionmentioning
confidence: 96%
“…For each experimental condition, 60 embryos or larvae were placed in triplicate (by each time period) in 20 cm-diameter glass Petri dishes containing 200 mL of test solution, which were entirely replaced every 48 h. Temperature between 20 ± 2°C and a 12:12-h light-to-dark photoperiod were maintained throughout the experiments, which lasted 504 h. Test solutions ranged between 0.001 and 0.005 and between 0.0005 and 0.075 mg of endosulfan L -1 for embryos and larvae, respectively. This concentration range was selected considering that the maximum exposure concentration was lower than the LC10 values obtained in our previous study (Svartz et al 2014). Tadpoles were fed with balanced fish food TetraColor (Tetra): Eighteen granules were placed in each Petri dish every 48 h. The uptake and wet weight were measured at three exposure times: 96, 240, and 504 h. At each time, 50 organisms were removed from each replicate, thoroughly washed with 200 mL of AS, blotted dry on absorbent paper, and then weighed and stored at -20°C for analytical assessment.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations